BLUE BIRD GROUP'S STRATEGIC COMMUNICATION IN INDUSTRIAL 4.0 ERA - M. Farid Aryaputra Tirtosudiro; Dasep Suryanto; Ria Anggelica Anadji (Sean Institute, 2023)
Blue Bird has a pretty big fleet, but in 2016, both the number of fleets and the amount of money it made went down because of competition from online cabs. Blue Bird Group needs to get more creative with how it markets its services so that people will want to use them again and they can stay in business like they did before online cars. The goal of this study is to look at how Blue Bird Group communicates strategically in the industrial age 4.0. The way of research used in this study is a literature review, which is a qualitative method. The data used came from other sources, like books, scientific works, and the results of past study. The steps of data analysis were collecting the data, reducing the amount of data, showing the data, and making conclusions. The results showed that Blue Bird Group's communication strategy for the industrial era 4.0 included getting people involved in the organization, changing business models and integrating technology, communication, and employee engagement, being responsive to customer preferences and needs, investing in technology, and forming partnerships. A communication strategy was also used to improve the quality of products and services, work with different places, set prices using technology, advertise, hand out coupons, and connect with the public through social media.